The influence of work-life balance, internal communication, and empowerment on employee performance with employee engagement as an intervening variable in star-rated hotels in Pangkalpinang - Bagas Olanda; Suhardi Suhardi; Siti Napisah (Economic: Journal Economic and Business, 2026)
The hospitality industry demands high-performance employees amidst operational dynamics and continuous service pressures. This study aims to analyze the influence of work-life balance, internal communication, and empowerment on employee performance, with employee engagement as an intervening variable, in a star-rated hotel in Pangkalpinang. A quantitative approach was used using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. Data were collected from 120 star-rated hotel employees selected through purposive sampling with a minimum tenure of one year. The results show that internal communication and empowerment have a positive and significant effect on employee engagement, while work-life balance has no significant effect on employee engagement. However, work-life balance has a significant direct effect on employee performance. In addition, employee engagement mediates the effect of internal communication and empowerment on employee performance, but does not mediate the effect of work-life balance. These findings confirm that in the hospitality context, relational and psychological factors of the organization are more effective in improving performance than work-life balance alone.